Adhesion of Candida biofilm cells to human epithelial cells and polystyrene after treatment with silver nanoparticles - Monteiro, Douglas Roberto [UNESP]; Negri, Melyssa; Silva, Sonia; Gorup, Luiz Fernando; Camargo, Emerson Rodrigues de; Oliveira, Rosario; Barbosa, Débora de Barros [UNESP]; Henriques, Mariana (Elsevier B.V., 2014)
This study investigated the adhesion to human epithelial cells and polystyrene surface of viable yeasts recovered from Candida biofilms treated with silver nanoparticles (SN). Biofilm resuspended Candida cells were added to HeLa cells or to empty wells of microtiter plates and the adhesion was verified using crystal violet staining. The adhesion of Candida cells was significantly reduced, mainly when biofilms were pretreated with 54 mu g/mL SN. These new findings allow to conclude that SN may induce changes in viable yeasts, which can decrease the dissemination of Candida infections, mainly in susceptible patients. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Candida; Epithelial cells; Polystyrene; Silver nanoparticles; Yeast adhesion